1967
DOI: 10.1039/j39670002432
|View full text |Cite
|
Sign up to set email alerts
|

The reactions of t-butyl peroxide with toluene derivatives

Abstract: The reactions of t-butyl peroxide with toluene derivatives, containing chloro-, bromo-, cyano-, methyl-, and phenylsubstituents in the alkyl side chain andp-halogeno-substituents in the nucleus, givevariable yields of the corresponding dehydro-dimers. Good yields are obtained with the p-halogeno-substituted cumenes, benzyl cyanide, p-chlorobenzyl cyanide, benzylidene dichloride, and p-bromoethylbenzene. a-Chloroethylbenzene, benzyl bromide, benzyl chloride, p-chlorobenzyl chloride, and p-tolunitrile give moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…1), while the intensity of ZnAl 2 O 4 phase decreases. The observed diffraction peaks of ZnAl 2 O 4 -doped TiO 2 result are consistent with the previously reported [6][7][8]10]. Furthermore, the peak positions of the phases shift slightly toward the higher angle with increasing x, which suggests a reduction in the unitcell dimension due to the improvement of crystallizability.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…1), while the intensity of ZnAl 2 O 4 phase decreases. The observed diffraction peaks of ZnAl 2 O 4 -doped TiO 2 result are consistent with the previously reported [6][7][8]10]. Furthermore, the peak positions of the phases shift slightly toward the higher angle with increasing x, which suggests a reduction in the unitcell dimension due to the improvement of crystallizability.…”
Section: Resultssupporting
confidence: 92%
“…It has been used as catalyst support, ceramic materials, electronics, and optical materials [9]. At present, some researchers studied the dielectric properties of ZnAl 2 O 4 doped with TiO 2 as microwave dielectric ceramics [6,[10][11][12][13]. Accordingly, they have found that ZnAl 2 O 4 doped with TiO 2 ceramics has excellent properties and has a very extensive prospect to be used as microwave substrates and for antenna applications in the future.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Tetrachlorotolan, however, has been obtained from trichlorotoluene using red phosphorus in the presence of hydroiodic acid (25), elemental sulfur ( 1 3 , di-tertiarybutyl peroxide (26), and finely powdered tin (27), all reducing systems for the generation of radicals. Considering these examples, in the light of our own experiments, it was possible that the coloured species formed with 1,2,5-triphenylphosphole in boiling a ,a ,a-trichlorotoluene was the radical species 6 thermally produced in equilibrium with the phosphonium salt 5, neither of which arise to any significant extent at ambient temperatures.…”
Section: Electron Spin Resonance Experimentsmentioning
confidence: 99%